196k views
8 votes
4

To eliminate the y terms from the following system of equations, the first
equation must be multiplied by 5 and the second equation must be
multiplied by 4.
x - 4y = 11
-3x + 5y = 25ها
If the statement is true, type true in the space provided, if it is false, replace the underline words with the words that will make the statement true.

User James Dean
by
5.8k points

1 Answer

8 votes

Answer:

True

Explanation:

x - 4y = 11 → (1)

- 3x + 5y = 25 → (2)

Multiply (1) by 5 and (2) by 4 to eliminate the y- term

5x - 20 y = 55 → (3)

- 12x + 20y = 100 → (4)

Add (3) and (4) term by term to eliminate y

- 7x + 0 = 155

- 7x = 155 ← y- term is eliminated

User Davydotcom
by
5.6k points